Freedom and Klugheit in Kant’s Anthropology Lectures - Holly Wilson (Con-textos Kantianos: International Journal of Philosophy, 2017)
Kant holds in his works on morality that prudence is not free, because only action under the moral law is free. He also holds that acting on prudent reasons is incompatible with the moral law. If one explores his lectures on anthropology, however, one has reason to believe that not only is prudent action free in some sense as freedom of choice, but it is also not incompatible with moral action, since it does not necessitate using other human beings as mere means, even though it is about using other human beings as ends to one’s happiness. This article will show how Kant holds these positions in his lectures on anthropology.